Sistem Informasi Standard Bill Of Material Quantity Genset di PT Conductorjasa Suryapersada (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2017)
Implementation of the control of Standard bill of material quantity is very important for business entities that aims to support the performance in running a production work according to management planning. High demand for generators requires proper inventory control because the organization spends enormous costs on inventory. PT Conductorjasa Suryapersada is a business entity located on Jl. Rungkut Industri IV/18, Surabaya which is made as research object. The problems that exist in PT Conductorjasa Suryapersada is that there is often a change of Standard bill of material which is not updated from time to time and material inventory that often runs out because ordering generator only based on estimation from previous month data so that happened accumulation or stock of material in warehouse. With the EOQ (Economic Order Quantity) method, then the comparison of the results between the initial policy of the company and after using the EOQ (Economic Order Quantity) method is obtained that can happen controlled inventory of material in the warehouse with minimum storage and saving cost of large enough By using EOQ (Economic Order Quantity) method.The result of the standard bill of material quantity information system is the creation of bomb data made more accurate because the system can detect the amount of material inventory in the warehouse so as not to run out for the assembly of generator assembly process which can be the bomb data of the generator assembly standard in accordance with the inventory of material goods warehouse.